Impact of defensins‐containing body cream on skin composition. (1st August 2022) - Eggerstedt, Michael; Torres‐Maldonado, Solymar; Danielian, Arman; Hwang, Song Hon Josh; Echanique, Kristen A.
Abstract: Background and Aims: Defensins are peptides capable of reactivating latent LGR6 stem cells in the basal layer. When applied topically, these peptides can reduce signs of skin aging and increase dermal thickness. This study investigates the effects of a topical defensin formulation on extremity skin composition. Methods: An open label, single arm clinical trial was conducted on participants with dry, photoaged, or dull skin. A defensin‐containing hand and body cream was applied twice daily for 6 weeks to the hands, forearms, elbows, and knees. Photographs and objective measurements of skin hydration, viscoelasticity (VE), retraction time (RT), thickness, density/transepidermal water loss (TEWL), as well as self‐evaluation of skin quality and characteristics were obtained pre‐ and post‐ intervention. Results: After the study period, RT decreased by 56% across all body sites ( p < 0.001) and VE improved at the elbow (125%, p = 0.009) and knee (110%, p < 0.001). Skin density also increased in all 4 body sites (40%, p < 0.001), while skin thickness increased at the elbow (29%, p = 0.03) and knee (17%, p = 0.04). Skin hydration increased at the elbow, knee, and forearm by 99%, 28%, and 16%, respectively ( p < 0.05), while TEWL improved at the elbow only (−39%, p = 0.02). Patients' self‐evaluations showed improvements in overall skin quality and in the domains of dryness, ashiness, wrinkling, pigmentation, redness, roughness, and discomfort ( p < 0.05). Conclusions: Following 6‐week use of a defensin‐containing cream, subjects reported significant improvement across many subjective skin domains. Similarly, objective measurements demonstrated significant improvement in skin architecture at select sites.